2021
DOI: 10.1021/acs.orglett.1c01022
|View full text |Cite
|
Sign up to set email alerts
|

Global Genome Mining Reveals a Cytochrome P450-Catalyzed Cyclization of Crownlike Cyclodipeptides with Neuroprotective Activity

Abstract: We conducted global genome mining of 162,672 bacterial genomes and identified 829 cyclodipeptide (CDP) biosynthesis gene clusters (BGC) containing a cytochrome P450 gene. Heterologous expression of BGC from Saccharopolyspora hirsuta DSM 44795 led to the identification of two novel crownlike CDPs, cyctetryptomycin A (4) and B (5), which possess unprecedented complex macrocycle and show neuroprotective activity. The two cytochrome P450s found in the BGC catalyze sequential reactions leading to the cyclization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 19 publications
0
47
0
Order By: Relevance
“…The presence of specific chemical moieties known to enhance bioactivities, such as the cationic amino acids and thioamides mentioned in this review [54,63], can be directly used for candidate prioritization. Targeting a biosynthesis enzyme with high substrate promiscuity or the ability to catalyze different reactions can be beneficial, as shown in the studies on nisin lanthipeptide heterologous expression [66], cytochrome P450 [51,55], and radical SAMs [57,65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of specific chemical moieties known to enhance bioactivities, such as the cationic amino acids and thioamides mentioned in this review [54,63], can be directly used for candidate prioritization. Targeting a biosynthesis enzyme with high substrate promiscuity or the ability to catalyze different reactions can be beneficial, as shown in the studies on nisin lanthipeptide heterologous expression [66], cytochrome P450 [51,55], and radical SAMs [57,65].…”
Section: Discussionmentioning
confidence: 99%
“…The heterologous expression of this BGC led to the description of the novel cyclodipeptides cyctetryptomycins A and B, which contain an unusual large macrocyclic core. Further bioassay testing showed that these compounds display potent neuroprotective activity [55]. Following this study, we were inspired by how prenylation can enhance the bioactivities of compounds and aimed to uncover new prenylated compounds by following the same pipeline.…”
Section: Hnmentioning
confidence: 99%
“…Guanitrypmycins. The rst identied product related to this class of C3-purine substituted PiNPs is guanitrypmycin C3-1 (244), which has an N1-C8 0 -linked guaninyl-DKP 245), 226 but also produce the two C3purine substituted PiNPs 12 and 246, which have a C3-C8 0 and C3-C2 0 linkage between guanine and hypoxanthine, respectively (Fig. 32A).…”
Section: C3-purine-substituted Pinpsmentioning
confidence: 99%
“…Functionally characterized CDPSs have been obtained essentially from three bacteria phyla, namely Actinobacteria, Firmicutes, and Proteobacteria. [18][19][20][21][22][23] Although the 2,5-DKPs generated by the action of CDPSs could incorporate 18 of the 20-proteogenic amino acids (with the exception of Lys and Asp), 19,21 the use of 26 non-canonical amino acids as substrates recently generated ca. 200 non-canonical CDPs.…”
Section: Biogenetic Generation Of Complexitymentioning
confidence: 99%
“…37,40 Radical-based mechanisms have also been proposed for the biogenesis of more complex bispyrrolidinoindoline dioxopiperazine natural products with crown-like structural arrangements. 23 The conformationally constrained DKP scaffold of dimeric dioxopiperazines are considered as privileged structures 43 since somehow mimic preferential peptide conformations, with two hydrogen bond donor and acceptor sites further favoring interactions with putative receptors. 44,45 The six-membered ring confers conformational rigidity and stability at low pH for this family of natural products.…”
Section: Biogenetic Generation Of Complexitymentioning
confidence: 99%